BUDIDAYA LEBAH MADU DI DESA TEGAL YOSO LAMPUNG TIMUR - Winarno, Gunardi D; Nugroho, Abi; Bintoro, Afif (MAKILA, 2024)
Tegal Yoso Village in Purbolinggo District, East Lampung, is the focus of empowerment by the TNWK Center through the Wana Karya Forest Farmers Group (KTH). Research in this village, carried out from 15 May to 13 June 2023, aims to identify the food types of Heterotrigona itama bees, understand feeding and communication behavior, and assess the economic value of selling bees and their impact on the economy. Villages were chosen because they represent communities that have significant bee logs. Apart from KTH, people can buy bee logs from individuals for around Rp. 750,000.00, or using trees with bee hives that are not used by the land owner, and can even obtain bee colonies by breaking them down. Explanation of the division of tasks in Heterotrigona itama bees, namely the Queen Bee Strata. The main task of the Queen Bee is to be responsible for reproduction in the bee colony. It is a female bee that was specially developed to be the leader of the colony. The Queen Bee's duties include laying eggs.